2020
DOI: 10.1200/jco.19.03091
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Phase II Study of Maintenance Pembrolizumab Versus Placebo After First-Line Chemotherapy in Patients With Metastatic Urothelial Cancer

Abstract: PURPOSE Platinum-based chemotherapy for first-line treatment of metastatic urothelial cancer is typically administered for a fixed duration followed by observation until progression. “Switch maintenance” therapy with PD-1 blockade at the time of chemotherapy cessation may be attractive for mechanistic and pragmatic reasons. PATIENTS AND METHODS Patients with metastatic urothelial cancer achieving at least stable disease on first-line platinum-based chemotherapy were enrolled. Patients were randomly assigned do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 23 publications
2
75
0
4
Order By: Relevance
“…A total of 2367 studies describing the correlations between ICIs and endocrine adverse events were retrieved; 1566 in the Pubmed database and 801 in the Embase database, while 130 duplicates were excluded. As a result, 2302 studies remained, and after skimming the titles and abstracts and reading the full texts, 26 RCTs 7–32 were obtained, comprising 13 824 patients (7786 in the intervention groups and 6038 in the control groups). The details of the screening process are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2367 studies describing the correlations between ICIs and endocrine adverse events were retrieved; 1566 in the Pubmed database and 801 in the Embase database, while 130 duplicates were excluded. As a result, 2302 studies remained, and after skimming the titles and abstracts and reading the full texts, 26 RCTs 7–32 were obtained, comprising 13 824 patients (7786 in the intervention groups and 6038 in the control groups). The details of the screening process are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The basic characteristics of 26 RCTs are shown in Table 1. Nivolumab was used in 8 studies 9–16 ; pembrolizumab was used in 10 studies 7,8,17,18,19–24 ; ipilimumab was used in 3 studies 25–27 ; tremelimumab was used in 2 studies 28,29 ; and atezolizumab, 30 avelumab, 31 and durvalumab 32 were used in 1 study, respectively. Of 26 studies, 2 7,8 were comparative analyses of different doses of the same drug and chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…A similar approach has been explored in a randomized phase 2 trial looking at maintenance pembrolizumab after first-line chemotherapy (HCRN GU14-182). 2 This trial similarly showed improvement in PFS; however, OS was not yet mature at the time of data analysis. It should be noted that crossover was permitted in the HCRN study, while this was not allowed in the current Javelin 100 study.…”
Section: Commentarymentioning
confidence: 95%
“…These results led to the recent FDA approval of avelumab switch maintenance therapy following first-line chemotherapy in patients with mUC. Similarly, the phase II HCRN GU14-182 study enrolled LA/mUC patients who achieved at least stable disease following first-line platinum-based chemotherapy and randomly assigned them to receive maintenance pembrolizumab versus placebo 13 . Patients receiving maintenance pembrolizumab demonstrated an improvement in median PFS compared with placebo (5.4 versus 3.0 months; HR 0.65).…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%